Chronic wasting disease (CWD) in cervids. (18th January 2017) - ; Ricci, Antonia; Allende, Ana; Bolton, Declan; Chemaly, Marianne; Davies, Robert; Fernández Escámez, Pablo Salvador; Gironés, Rosina; Herman, Lieve; Koutsoumanis, Kostas; Lindqvist, Roland; Nørrung, Birgit; et al.
Abstract: In April and May of 2016, Norway confirmed two cases of chronic wasting disease (CWD) in a wild reindeer and a wild moose, respectively. In the light of this emerging issue, the European Commission requested EFSA to recommend surveillance activities and, if necessary, additional animal health risk‐based measures to prevent the introduction of the disease and the spread into/within the EU, specifically Estonia, Finland, Iceland, Latvia, Lithuania, Norway, Poland and Sweden, and considering seven wild, semidomesticated and farmed cervid species (Eurasian tundra reindeer, Finnish (Eurasian) forest reindeer, moose, roe deer, white‐tailed deer, red deer and fallow deer). It was also asked to assess any new evidence on possible public health risks related to CWD. A 3‐year surveillance system is proposed, differing for farmed and wild or semidomesticated cervids, with a two‐stage sampling programme at the farm/geographically based population unit level (random sampling) and individual level (convenience sampling targeting high‐risk animals). The current derogations of Commission Implementing Decision (EU) 2016/1918 present a risk of introduction of CWD into the EU. Measures to prevent the spread of CWD within the EU are dependent upon the assumption that the disease is already present; this is currently unknown. The measures listed are intended to contain (limit the geographic extent of a focus) and/or to control (actively stabilise/reduce infection rates in an affected herd or population) the disease where it occurs. With regard to the zoonotic potential, the human species barrier for CWD prions does not appear to be absolute. These prions are present in the skeletal muscle and other edible tissues, so humans may consume infected material in enzootic areas. Epidemiological investigations carried out to date make no association between the occurrence of sporadic Creutzfeldt–Jakob disease in humans and exposure to CWD prions.